Physiological and Transcriptomic Changes in the Hypothalamic-Neurohypophysial System after 24 h of Furosemide-Induced Sodium Depletion - Dutra, Sabrina G. (2020)
Background/Aims: Furosemide is a loop diuretic widely used in clinical practice for the treatment of oedema and hypertension. The aim of this study was to determine physiological and molecular changes in the hypothalamic-neurohypophysial system as a consequence of furosemide-induced sodium depletion. Methods: Male rats were sodium depleted by acute furosemide injection (10 and 30 mg/kg) followed by access to low sodium diet and distilled water for 24 h. The renal and behavioural consequences were evaluated, while blood and brains were collected to evaluate the neuroendocrine and gene expression responses. Results: Furosemide treatment acutely increases urinary sodium and water excretion. After 24 h, water and food intake were reduced, while plasma angiotensin II and corticosterone were increased. After hypertonic saline presentation, sodium-depleted rats showed higher preference for salt. Interrogation using RNA sequencing revealed the expression of 94 genes significantly altered in the hypothalamic paraventricular nucleus (PVN) of sodium-depleted rats (31 upregulated and 63 downregulated). Out of 9 genes chosen, 5 were validated by quantitative PCR in the PVN (upregulated: Ephx2, Ndnf and Vwf; downregulated: Caprin2 and Opn3). The same genes were also assessed in the supraoptic nucleus (SON, upregulated: Tnnt1, Mis18a, Nr1d1 and Dbp; downregulated: Caprin2 and Opn3). As a result of these plastic transcriptome changes, vasopressin expression was decreased in PVN and SON, whilst vasopressin and oxytocin levels were reduced in plasma. Conclusions: We thus have identified novel genes that might regulate vasopressin gene expression in the hypothalamus controlling the magnocellular neurons secretory response to body sodium depletion and consequently hypotonic stress.